Specific sensorimotor interneuron circuits are sensitive to cerebellar-attention interactions - Mirdamadi, Jasmine L.; Meehan, Sean K. (Frontiers in Human Neuroscience, 2022)
Background: Short latency afferent inhibition (SAI) provides a method to investigate mechanisms of sensorimotor integration. Cholinergic involvement in the SAI phenomena suggests that SAI may provide a marker of cognitive influence over implicit sensorimotor processes. Consistent with this hypothesis, we previously demonstrated that visual attention load suppresses SAI circuits preferentially recruited by anterior-to-posterior (AP)-, but not posterior-to-anterior (PA)-current induced by transcranial magnetic stimulation. However, cerebellar modulation can also modulate these same AP-sensitive SAI circuits. Yet, the consequences of concurrent cognitive and implicit cerebellar influences over these AP circuits are unknown. Objective: We used cerebellar intermittent theta-burst stimulation (iTBS) to determine whether the cerebellar modulation of sensory to motor projections interacts with the attentional modulation of sensory to motor circuits probed by SAI. Methods: We assessed AP-SAI and PA-SAI during a concurrent visual detection task of varying attention load before and after cerebellar iTBS. Results: Before cerebellar iTBS, a higher visual attention load suppressed AP-SAI, but not PA-SAI, compared to a lower visual attention load. Post-cerebellar iTBS, the pattern of AP-SAI in response to visual attention load, was reversed; a higher visual attention load enhanced AP-SAI compared to a lower visual attention load. Cerebellar iTBS did not affect PA-SAI regardless of visual attention load. Conclusion: These findings suggest that attention and cerebellar networks converge on overlapping AP-sensitive circuitry to influence motor output by controlling the strength of the afferent projections to the motor cortex. This interaction has important implications for understanding the mechanisms of motor performance and learning.